SISTEM INFORMASI GEOGRAFIS PENANGANAN JALAN NASIONAL PROVINSI D. I. YOGYAKARTA - , Choirul Z; , Dr. Ir. H. Muslikh, M.Sc, M.Phil. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Road as a part of the national transportation system has a very important role in supporting the economic, social, cultural and environmental aspects. The importance function of road requires the government to have a strategic plan and road handling rapidly, precisely and accurately. It is necessary to prepare a national road database based on Geographic Information System that is able to accommodate the needs of the policy holder. The preparation of Geographic Information System in handling national roads conducted in this research was for 37 segments of national road under the responsibility of P2JN of D.I. Yogyakarta province. The purpose of this research was to analyze the system condition of national roads based on the value of IRI under the responsibility of P2JN of D.I. Yogyakarta province and to develop a Geographic Information System in Handling National Roads of D.I. Yogyakarta province under the responsibility of P2JN of D.I. Yogyakarta province. In order to achieve the desired result, the step taken in this research was to conduct a preliminary study first, then collect the primary data and secondary data, select the system then prepare a program that consists of arrangement of the system, the design of the system, the components that are equipped with the data of the roads, the road conditions, the handling and the road maps. Then do the presentation of the results in the form of internet-based Geographic Information System and examine/evaluate the program to generate an optimal system. Conclusions and suggestions could be obtained after the process were completed. The results of this research for the national roads condition under the responsibility P2JN of D.I. Yogyakarta province based on IRI obtained the percentage of the road conditions is 98.55% and the condition is not stable at 1.45% of the total length of 223.161 km. This research resulted Geographic Information System that contains of stationing system information, the data of the roads, the data of road conditions, and the national roads handling under the responsibility of P2JN of D.I. Yogyakarta province. Keywords: P2JN, GIS, National Roads, D.I Yogyakarta Province